HUBUNGAN TINGKAT PENGETAHUAN DENGAN PERILAKU PADA MAHASISWA KEPERAWATAN ANESTESIOLOGI TENTANG DIFFICULT AIRWAY MANAGEMENT DENGAN ANESTESI UMUM - Rosyida, Umiatun (Jurnal Ilmiah Kesehatan Media Husada, 2025)
Abstract Background: Difficult airway is defined as a clinical situation where the anesthesiologist has difficulty performing ventilation, intubation, or both. Objective: To determine the relationship between the level of knowledge and behavior in anesthesiology nursing students regarding difficult airway management with general anesthesia. Research Method: This research uses quantitative methods with a correlation analytical research design with a cross-sectional approach. Sampling technique with a total sampling of 141 respondents with inclusion and exclusion criteria. Data analysis was carried out using the Spearman Rank test. Research Results: The level of knowledge of anesthesiology nursing students regarding difficult airway management with general anesthesia was in the good category as many as 84 (59.6%) students. Meanwhile, 83 (58.9%) students had good behavior. Based on statistical analysis using the Spearman Rank test, there is a significant relationship, with a low positive correlation (r = 0.264), between knowledge and behavior (p-value 0.002 <0.05) indicating that Ha is accepted. Conclusion: There is a significant relationship between the level of knowledge and behavior of anesthesiology nursing students regarding difficult airway management. Suggestion: It is hoped that this will provide additional information for students and future researchers regarding the relationship between the level of knowledge and behavior in anesthesiology nursing students regarding difficult airway management. Keywords: Level of Knowledg; Behavior; Anesthesiology Nursing Students; Difficult Airway Management. Abstrak Latar Belakang: Difficult airway didefinisikan sebagai situasi klinis dimana ahli anestesi kesulitan saat melakukan ventilasi, intubasi, atau keduanya. Tujuan: Mengetahui hubungan tingkat pengetahuan dengan perilaku pada mahasiswa keperawatan anestesiologi tentang difficult airway management dengan anestesi umum. Metode Penelitian: Penelitian ini menggunakan metode kuantitatif dengan desain penelitian analitik korelasi dengan pendekatan cross sectional. Tehnik pengambilan sampel dengan total sampling yang berjumlah 141 responden dengan kriteria inklusi dan eksklusi. Analisis data yang dilakukan menggunakan uji Spearman Rank. Hasil Penelitian: Tingkat pengetahuan mahasiswa keperawatan anestesiologi tentang difficult airway management dengan anestesi umum dengan kategori baik sebanyak 84 (59,6%) mahasiswa. Sedangkan mahasiswa yang memiliki perilaku baik sebanyak 83 (58,9%) mahasiswa. Berdasarkan analisis statistik menggunakan uji Spearman Rank terdapat hubungan yang signifikan, dengan arah korelasi positif yang rendah (r = 0,264), antara pengetahuan dengan perilaku (p-value 0,002<0,05) menunjukkan bahwa Ha diterima. Simpulan: Terdapat hubungan yang signifikan antara tingkat pengetahuan dengan perilaku mahasiswa keperawatan anestesiologi tentang difficult airway management. Saran: Diharapkan dapat menjadi tambahan informasi kepada mahasiswa dan peneliti selanjutnya mengenai bagaimana hubungan tingkat pengetahuan dengan perilaku pada mahasiswa keperawatan anestesiologi tentang difficult airway management. Kata Kunci: Tingkat Pengetahuan; Perilaku; Mahasiswa Keperawatan Anestesiologi; Difficult Airway Management.